If we expand and simplify 2(x+5)+3(x−2)2(x+5)+3(x−2)2(x+5)+3(x−2) we will get 2(x+5)+3(x−2)=2x+10+3x−6=5x+42(x+5)+3(x−2)=2x+10+3x−6=5x+42(x+5)+3(x−2)=2x+10+3x−6=5x+4 What does expand and simplify mean? Expand...
8. Expand and simplify each of the following expressions.(a)4u-3(2u-5v)(b)-2a-3(a-b)(c) 7m-2n-2(3n-2m)(d) 5(2x+4)-3(-6-x)(e)-4(a-3b)-5(a-3b)(f) 5(3p-2q)-2(3p+2q)(g)x+y-2(3x-4y+3)(h) 3(p-2q)-4(2p-3q-5)(i) 9(2a+4b-7c)-4(b-c)-7(-...
58_expand-and-factorise Edexcel GCSE Mathematics (Linear) – 1MA0 ALGEBRA:EXPAND & FACTORISE Materials required for examination Items included with question papers Ruler graduated in centimetres and Nil millimetres, protractor, compasses,pen, HB pencil, eraser.Tracing paper may be used.Instructions...
百度试题 结果1 题目(a) Expand the brackets and simplify.(2x+3)(2x+1)(a) 4+8. +3 as final answer 相关知识点: 试题来源: 解析 4x^2+8x+3 as final answer 反馈 收藏
Since - 8x and 15x are similar terms, we may combine them to obtain 7x. In this example we were able to combine two of the terms to simplify the final answer. Here again we combined some terms to simplify the final answer. Note that the order of terms in the final answer does not ...
Answer and Explanation:1 Brackets in general mean a function that encloses various other functions. According to the basic BODMAS rule: B -> Brackets /O -> Order, i.e... Learn more about this topic: How to Simplify an Expression with Parentheses & Exponents ...
(b) (i) Expand (1+2x)2 in ascending powers of x, as far as the term in x3. Simplify each term. [2](ii) Use your expansion to show that the value of 0.9820 is 0.67 to 2 decimal places.[2] 相关知识点: 试题来源: 解析 (i) 1+40x+760x²+9120x³(ii) 1+40(-0.01)+...
The first step is to simplify what is inside the parentheses. As mentioned earlier, an expression may have a different value if parentheses are not used. We saw that 12 - (3 + 4) = 5, but it was stated that without parentheses 12 - 3 + 4 = 13. This is due to the following rul...
(a) (2 x)3=23 x3=8 x3(b) (− 2 x)2=(− 2)2 x2=4 x2(c) (− x)2=(− 1)2 x2=1·x2=x2 (d) (− x)3=(− 1)3 x3=(− 1) x3=− x3We may use both Theorems 1 and 2 to simplify polynomials....
Chapter 10/ Lesson 4 151K Understand how to evaluate logarithmic expressions, know how to solve logarithmic equations, and explore the various properties of logarithms that are used in evaluating logarithm problems. Explore our homework questions and answers library ...